2016
DOI: 10.1007/s10457-016-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of non-timber forest products (NTFPs) to rural household revenues in two villages in south-eastern Burkina Faso

Abstract: The contribution of non-timber forest products (NTFPs) to rural household revenues in two villages in southeastern Burkina Faso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Hence, this study found that the annual value of NTFPs' incentives for forest conservation activities was around US$0.95/ha (US$95/km 2 ). Comparing to [3], who found direct costs of conserving two of Kenya's wetland National Parks were some Ksh 20 million per year (US$333,333, the exchange rate in 1998). Comparing to [32], who found that the annual costs of conservation vary enormously from less than US$0.1 to greater than US$1,000,000 per km 2 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hence, this study found that the annual value of NTFPs' incentives for forest conservation activities was around US$0.95/ha (US$95/km 2 ). Comparing to [3], who found direct costs of conserving two of Kenya's wetland National Parks were some Ksh 20 million per year (US$333,333, the exchange rate in 1998). Comparing to [32], who found that the annual costs of conservation vary enormously from less than US$0.1 to greater than US$1,000,000 per km 2 .…”
Section: Discussionmentioning
confidence: 93%
“…Non-timber forest products (NTFPs) are the primary resources from forests in developing countries [1][2][3]. Extraction of non-timber forest products for both subsistence and trade remains common and widespread today because it is highly significant to the rural and national economies in provision of food, material, construction, energy, cash income, employment, and other benefits [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We presume that increased grazing pressure is the major driver of these shifts, leading to a distinct homogenization of herbaceous vegetation types by favoring widely distributed and wide‐ranging annual plant species and to a decrease of valued perennial fodder species with detrimental consequences for livestock breeding and the livelihoods dependent on it (Leßmeister et al., ). Further studies on the impacts of land use are needed to evaluate the consequences for biodiversity and livelihoods on a broader scale.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, an increasing human population and growing cash crop production have led to the expansion of agricultural lands, to a shortening of fallow periods, and to increasing grazing pressure (Hahn‐Hadjali et al., ) in West Africa, resulting in an impoverishment of soils (Gray, ) and vegetation (Ouedraogo et al., ; Wittig, König, Schmidt, & Szarzynski, ). Since savanna biodiversity is important for human well‐being and serves as a source of household income (Leßmeister et al., ), land use change can have direct and negative impacts on local livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of locally collected wild resources, often termed non-timber forest products (NTFPs), contributes to all facets of rural life, including for energy, construction, food, health (via medicines), crafts and utilitarian items, decoration, as well as cultural products and a sense of identity [22]. A global synthesis concluded that NTFPs contribute, on average, 28% of household cash and non-cash income [23], and in some contexts or households, the contribution is on a par with, or even exceeds, agricultural income [24][25][26][27]. Thus, the availability of NTFPs is vital for many rural communities, including in the Wild Coast region of South Africa covered by this paper [15,28,29], and there is some evidence that it is especially so for poorer households and regions [30][31][32].…”
mentioning
confidence: 99%